2019
DOI: 10.3390/w11030590
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Index Analysis Approach to Heavy Metal Pollution Assessment in River Sediments in the Ponce Enríquez Area, Ecuador

Abstract: The area of Ponce Enríquez, Southern Ecuador, is one of the most important artisanal and small scale gold mining (ASGM) areas in the country, where informal mining operations can be found using amalgamation technique, even though it has been prohibited since 2010. Considering the potential impact of these mining operations, the present research focused on heavy metal pollutants in subsurface sediments at 214 sampling locations from several detailed sampling campaigns in the rivers Fermín, Fermín Norte, Guanach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The I geo mean of Cu, Pb and Zn were below 2 (unpolluted to moderately polluted) while the values of As and Cd were above level 4; heavily to extremely polluted. The I geo values detected in this study were similar to those reported by Aguilar et al [20]. Furthermore, the I geo values in the study area were in the same range as observed in the Colombia, Brazil, Iran and China mining areas [39]- [42], with moderate to severe degree of pollution where As-Cd-Cu metals are the most disturbing contaminants.…”
Section: Geo-accumulation Indexsupporting
confidence: 90%
“…The I geo mean of Cu, Pb and Zn were below 2 (unpolluted to moderately polluted) while the values of As and Cd were above level 4; heavily to extremely polluted. The I geo values detected in this study were similar to those reported by Aguilar et al [20]. Furthermore, the I geo values in the study area were in the same range as observed in the Colombia, Brazil, Iran and China mining areas [39]- [42], with moderate to severe degree of pollution where As-Cd-Cu metals are the most disturbing contaminants.…”
Section: Geo-accumulation Indexsupporting
confidence: 90%
“…Aguilar Pesantes et al. (2019) in the south of Ponce Enríquez investigated the pollution of river sediments by heavy metals (Cu, Pb, Zn, Ni, As, Cd, Sb, Sr, and Hg). The results of all indices showed that the concentration of heavy metals in sediments was high.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that very high concentrations of Cu (1,114 mg/kg) were found in the sediments, indicating high contamination of the area with heavy metals. Aguilar Pesantes et al (2019) in the south of Ponce Enríquez investigated the pollution of river sediments by heavy metals (Cu, Pb, Zn, Ni, As, Cd, Sb, Sr, and Hg). The results of all indices showed that the concentration of heavy metals in sediments was high.…”
mentioning
confidence: 99%
“…In this current study, it was found that the order of the CV % for heavy metal element from high to low was Cr > Ni > Pb > Cd > Cu > Zn. In some researches, it has been shown that high Ni level is caused by parent material and Pb content is caused by particle from surrounding lead acid battery factory (Pesantes et al, 2019). In addition, mean value of PERI was found 90.91 which indicate as low potential ecological risk in general for all soil samples.…”
Section: Soil Physical and Chemical Properties And Heavy Metalsmentioning
confidence: 98%